Postwar politics in the G-7 orders and eras in comparative perspective - Shafer, Byron E. 1938- (Univ. of Wisconsin Press, 1996)
Postwar Politics in the G-7 provides a condensed introduction to the politics of each of the seven nations, focusing on the main political events of the last fifty years and the factors that shaped the ways each country handled those events. By presenting these accounts in a precisely parallel fashion, this volume highlights similarities and differences among the nations. Concluding chapters reassemble these comparisons for all seven of the nations together. Among the most interesting findings are the rise of an activist politics, the continuing influential role of electoral systems, and the presence of divided governance nearly everywhere. Such a carefully constructed interpretation of postwar politics highlights potentially critical elements and provides comparative insights that are essential for understanding the Group of Seven nations